Statistics in High School: a potentially meaningful material for teaching the subject - Quedi, Rejane Padilha; Darroz, Luiz Marcelo; Rosa, Cleci Teresinha Werner da (Universidade Estadual de Campinas, 2020)
This study presents the results of an investigation that aimed to identify how a didactic sequence based on the Meaningful Learning Theory may be considered a potentially meaningful material for studying statistics in High School. The sequence was presented to a group of High School mathematics teachers. The data was collected using the logbook created by the research teacher and semi-structured interviews performed with the teachers. The data was analyzed in the following three a priori categories: relationship of the contents in the didactic sequence with students’ previous knowledge; progressive differentiation and integrative reconciliation; materials used and proposal structure. As a result, it was noted that the didactic sequence proposed might be considered a potentially meaningful material for the study of statistics, considering it favors the relationship of students’ previous knowledge with the topics addressed and allows establishing connections with such knowledge.